Application of the Finite element methods on the staking process of staking fasteners - Tofall, Miriam; Merklein, Marion; Plettke, Raoul (Key Engineering Materials, 2011)
The increasing use of new materials with varying thicknesses within the automotive industry creates high demands on joining elements such as staking fasteners. Simultaneously statements about the feasibility of the design with joining elements already in the early stage of the development are necessary. The challenge is to define suitable element geometry, tool geometry and process parameters. To meet those requirements, a good understanding of the staking process is inevitable. According to the state of the art the examinations regarding the performance of staking fasteners under different conditions are totally conducted experimentally. This trial-and-error procedure leads to an extensive financial effort and to long development times for new elements. It is furthermore not possible to observe all influences of different process parameters. In the field of mechanical engineering the use of numerical simulation for complex constructions is a common technique. This paper deals with the applicability of the finite element method (FEM) on the joining of sheet metals with staking fasteners. In this matter the FEM is used to get scientific insights in the staking process and is also used to identify influencing variables and their interactions. © (2011) Trans Tech Publications.
LFT Import::2019-07-29 (1645)
Keywords: FEM; Mechanical joining; Self-piercing fastener

Ermittlung funktioneller Zusammenhänge beim Fügen von Stanzmuttern und Blechhalbzeugen - Weiss, Miriam (Friedrich-Alexander-Universität Erlangen-Nürnberg (FAU), 2019)
Der zunehmende Einsatz moderner, insbesondere höher- und hochfester Werkstoffe zwingt die Stanzmuttertechnologie zu einem ständigen Weiterentwicklungsdruck. In der Praxis erfolgt die Durchführung anwendungstechnischer Untersuchungen rein experimentell. Dieses Trial-and-Error-Prinzip führt zu extrem langen Entwicklungszeiten. Zudem fehlt es an einem grundlegenden Prozessverständnis. Im Rahmen dieser Arbeit wurde durch die Anwendung der numerischen Simulation ein breites Verständnis des Fügeprozesses von Stanzmutterverbindungen und des Versagensverhaltens entwickelt. Durch die Werkstoffflussanalyse in Abhängigkeit des Prozessfortschritts wurden funktionelle Zusammenhänge zwischen geometrischer Verbindungsausbildung und mechanischer Verbindungsfestigkeit ermittelt und Maßnahmen zur werkstoffspezifischen Adaption von Stanzmutterverbindungen, insbesondere zur Erweiterung der Verfahrensgrenzen, identifizier
Keywords: mechanisches Fügen; numerische Fügeprozesssimulation; Stanzmutter

Numerical simulation of the staking process of clinching fasteners - Weiss, Miriam; Merklein, Marion; Plettke, Raoul (Proceedings SCT2011, 2011)
LFT Import::2019-08-05 (1648)